Crime and its victims what we can do - Van Ness, Daniel W. 1949- (Leicester, UK IVP, 1986)
Includes bibliographical references and index.
Donated by Pieter Dijkstal, 5/2003
Keywords: Justice -- religious aspects -- Christianity